Pengelompokan Kelelawar Pemakan Buah dan Nektar Berdasarkan Karakteristik Jenis Pakan Polen di Kebun Raya Bogor, Indonesia - Soegiharto, Sri; Kartono, Agus P.; Maryanto, Ibnu (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTThe Grouping of Fruit Bats Based on Pollend Type Characterized as Food Resources inBogor Botanical Garden, Indonesia. A study was conducted to identify pollen consummedby fruits bat in Bogor Botanical Garden from March 2008 to June 2009. The types of crown ofthe flower, pollen and pollen size which chosen by fruit bats were analysed by using highdetrended canonical correspondent. The result indicated that there are three major groups ofbats based on the similarities of food type or flower resources consumed by fruit bats. Thegroups were (1) males of Macroglossus sobrinus and the females of Eonycteris spelaea, (2)Cynopterus brachyotis and the females of C. minutus, and (3) males and females of C.titthaheileus, females of C. brachyotis and Macroglossus sobrinus, males of C. sphinx and C.minutus, and females of C. sphinx.Key words: Megachiroptera, pollend, seed distribution,